(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The problem of understanding the concept of multiplication at the primary school level is a significant challenge that can hinder students’ education if not addressed. Besides, literacy culture needs special attention because many students still need help in reading activities due to a lack of interest. This is due to the perception that reading is boring and the need for more support from the environment, including parents. This article discusses introducing educational games oriented towards numeracy literacy skills in fifth-grade students of SD Negeri 13 Kota Sorong through a campus teaching program. There are four stages in implementing the program: Situation Analysis/Partner Problem Study (Pre-Test), Preparation and Creation of Educational Games, Implementation/Introduction of Educational Games, and Program Implementation Results (Post-Test). The data were from the Campus Teaching Program Batch 7 using direct observation and interviews. Then, direct observation of the teaching and learning process is also carried out to determine students’ competence during this program. Based on the pre-test and post-test of the class Minimum Competency Assessment (AKM) conducted at the beginning and end of the activity, data obtained from students who experienced an increase in literacy as many as eight people (50%) remained as many as three people (18.75%). They decreased by five people (31.25%). Meanwhile, for numeracy, the number of students who experienced an increase was nine people (56.25), as many as one person (6.25%), and those who experienced a decrease were six people (37.5%). The results showed that the educational game improved some students’ literacy and numeracy skills, although some experienced a decline in both skills.